Evaluation of the abdominal wall cicatrization of rabbits exposed to nicotine and undergone abdominoplasty using nylon thread or cyanoacrylate - Costa,Luciano Assis (2012)
PURPOSE: To compare the wound healing of the abdominal wall of rabbits exposed to nicotine and submitted to abdominoplasty using 2-octyl cyanoacrylate or nylon thread for the surgery suture. METHODS: Thirty two rabbits were used. They were divided in subgroups: A1, A2, B1 e B2. Group A received saline 0.9%; group B received nicotine, both groups for 14 days before surgery. We performed an abdominoplasty with a nylon suture into the A1 and B1 subgroups; as for A2 and B2 groups the suture was performed with cyanoacrylate. The euthanasia happened in the 14th post-operative day. After, we evaluated: swollen process, fibroblast proliferation, collagen, neovascularization, and macroscope and microscope epithelization of the scars. RESULTS: We observed the presence of eosinophils in all scars exposed to the cyanoacrylate, and a significant increase of neovascularization in the subgroup B2 comparing to the A2 one (p=0.037). The other variables haven't showed any statistical difference. CONCLUSIONS: Nicotine hasn't influenced the swollen process, the fibroblast proliferation, the presence of collagen, neither the epithelialization. The neovascularization showed cicatricial immaturity when comparing group A2 to group B2. The eosinophils in the scars repaired with glue showed that the substance has acted as an allergen.